Early Diagnosis of Tularemia by Flow Cytometry, Czech Republic, 2003-20151 - Chrdle, Aleš; Tinavská, Pavlína; Dvořáčková, Olga; Filipová, Pavlína; Hnetilová, Věra; Žampach, Pavel; Batistová, Květoslava; Chmelík, Václav; Semper, Amanda E; Beeching, Nick J (Emerging infectious diseases, 2019)
We retrospectively assessed the utility of a flow cytometry-based test quantifying the percentage of CD3+ T cells with the CD4-/CD8- phenotype for predicting tularemia diagnoses in 64 probable and confirmed tularemia patients treated during 2003-2015 and 342 controls with tularemia-like illnesses treated during 2012-2015 in the Czech Republic. The median percentage of CD3+/CD4-/CD8- T cells in peripheral blood was higher in tularemia patients (19%, 95% CI 17%-22%) than in controls (3%, 95% CI 2%-3%). When we used 8% as the cutoff, this test's sensitivity was 0.953 and specificity 0.895 for distinguishing cases from controls. The CD3+/CD4-/CD8- T cells increased a median of 7 days before tularemia serologic test results became positive. This test supports early presumptive diagnosis of tularemia for clinically suspected cases 7-14 days before diagnosis can be confirmed by serologic testing in regions with low prevalences of tularemia-like illnesses.
Keywords: dospělí; CD3 Complex; Female; dítě; průtoková cytometrie; Adult; ženské pohlaví; antigeny CD3; mladý dospělý; tularemie; Adolescent; lidé; Sensitivity and Specificity; Flow Cytometry; studie případů a kontrol; Aged, 80 and over; Tularemia; senzitivita a specificita; T-lymfocyty; časná diagnóza; retrospektivní studie; CD4-CD8 Ratio; Male; Case-Control Studies; Aged; Czech Republic; sérologické testy; Young Adult; Early Diagnosis; Česká republika; lidé středního věku; Child; senioři nad 80 let; Serologic Tests; senioři; mužské pohlaví; T-Lymphocytes; poměr CD4 a CD8 lymfocytů; Retrospective Studies; Middle Aged; mladiství; Humans